Investigação da correlação da variabilidade da frequência cardíaca e o nível de estresse em canteiro de obras da construção civil, sob a ação de ruídos - Mayer, Sergio Luis Hernandez (2021)
This study presents an investigation carried out in a civil construction work environment, where employees are under exposure to high levels of sound pressure, which can cause physical and mental stress complications. The goal was to track the Heart Rate Variability (HRV) and correlate it to measure the physiological stress caused by the occurrence of noise. The research conducted can be classified as exploratory, crosssectional, quali-quantitative and descriptive, with data collected in real time in an actualwork environment, from 24 participants aged 27 to 53 years. A complete anamnesis of health conditions and a questionnaire of the Work Stress Scale (TSS) were performed. Body composition was also measured, hemodynamic assessment was performed, and Heart Rate Variability was monitored in the moments with and without noise. The data from the heart rate monitor were captured and filtered through the WCS Pulse software and analyzed using the Kubios HRV software. BioEstat software was used for statistical analysis, verifying the data normality using the Shapiro-Wilk test. The normal data were correlated by Pearson’s test and the non-parametric data by Spearman’s test. The samples from the periods with and without the presence of noise, by the Paired Student t-test and the Wilcoxon test. A p-value of less than 0.05 was considered. The evidences found in the research participants’ autonomic activity (ANS) alteration suggest that it is an indication of an association with the occurrence of the noises.